2020
DOI: 10.1093/eurheartj/ehaa192
|View full text |Cite
|
Sign up to set email alerts
|

Functional tricuspid regurgitation of degenerative mitral valve disease: a crucial determinant of survival

Abstract: Aims  To assess functional tricuspid regurgitation (FTR) determinants, consequences, and independent impact on outcome in degenerative mitral regurgitation (DMR). Methods and results  All patients diagnosed with isolated DMR 2003–2011, with structurally normal tricuspid leaflets, prospective FTR grading and systolic pulmonary artery pressure (sPAP) estimation by Doppler echocardiography at diagnosis were identified and long-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(32 citation statements)
references
References 39 publications
0
27
0
Order By: Relevance
“…A meta-analysis of 1,328 TAVI and 1, 001 MitraClip ® patients concluded that moderate-to-severe TR was a relevant determinant for increased mortality in left ventricular valvular heart disease [29]. Whether observed differences in survival between FMR and DMR patients in our study are subject to statistical bias, published data on surgically or medically treated DMR patients concluded that concomitant TR could also be a relevant determinant of survival in these patients [8] -or are caused by the completely different pathophysiology of MR etiologies as well as an impact of post-interventional changes in TMVR patients, has to be addressed by future analyses.…”
Section: Discussionmentioning
confidence: 45%
See 3 more Smart Citations
“…A meta-analysis of 1,328 TAVI and 1, 001 MitraClip ® patients concluded that moderate-to-severe TR was a relevant determinant for increased mortality in left ventricular valvular heart disease [29]. Whether observed differences in survival between FMR and DMR patients in our study are subject to statistical bias, published data on surgically or medically treated DMR patients concluded that concomitant TR could also be a relevant determinant of survival in these patients [8] -or are caused by the completely different pathophysiology of MR etiologies as well as an impact of post-interventional changes in TMVR patients, has to be addressed by future analyses.…”
Section: Discussionmentioning
confidence: 45%
“…In 35% of the patients, concomitant TR was reduced. Recently, a large registry comprising more than 5, 000 DMR patients demonstrated that severity of concomitant TR is a relevant inverse predictor of long-term survival of these patients regardless of a medical or surgical management strategy regarding MR [8]. While symptomatic and prognostic benefits have been recently proven for edge-to-edge TMVR for FMR in a multi-centric prospective trial in the US [19], the discussion on optimal patient selection is still on-going, since another prospective trial with similar design did not confirm these results [20].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The long-time accepted idea that tricuspid regurgitation (TR) is a benign valvular condition has been deeply rebutted by almost one decade of insights into its epidemiological and clinical implication. While trivial TR is a common finding during routine echocardiography examination of asymptomatic subjects and is considered almost a physiological condition (1), most recent data suggest that at least moderate TR is a frequent condition too, worsening mid and long-term survival, particularly in patients >75 years old, and in those suffering from left ventricular systolic dysfunction (LVSD) (2)(3)(4)(5).…”
Section: Introductionmentioning
confidence: 99%